Bacterial Phage Receptors, Versatile Tools for Display of Polypeptides on the Cell Surface - Etz, Hildegard (American Society for Microbiology, 2001)
Four outer membrane proteins of Escherichia coli were examined for their capabilities and limitations in displaying heterologous peptide inserts on the bacterial cell surface. The T7 tag or multiple copies of the myc epitope were inserted into loops 4 and 5 of the ferrichrome and phage T5 receptor FhuA. Fluorescence-activated cell sorting analysis showed that peptides of up to 250 amino acids were efficiently displayed on the surface of E. coli as inserts within FhuA. Strains expressing FhuA fusion proteins behaved similarly to those expressing wild-type FhuA, as judged by phage infection and colicin sensitivity. The vitamin B(12) and phage BF23 receptor BtuB could display peptide inserts of at least 86 amino acids containing the T7 tag. In contrast, the receptors of the phages K3 and λ, OmpA and LamB, accepted only insertions in their respective loop 4 of up to 40 amino acids containing the T7 tag. The insertion of larger fragments resulted in inefficient transport and/or assembly of OmpA and LamB fusion proteins into the outer membrane. Cells displaying a foreign peptide fused to any one of these outer membrane proteins were almost completely recovered by magnetic cell sorting from a large pool of cells expressing the relevant wild-type platform protein only. Thus, this approach offers a fast and simple screening procedure for cells displaying heterologous polypeptides. The combination of FhuA, along with with BtuB and LamB, should provide a comprehensive tool for displaying complex peptide libraries of various insert sizes on the surface of E. coli for diverse applications.